Structuring of Energy Resources and Strategy for Development of Power Engineering Industry in Vietnam - Thuy Nga Nguyen (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2011)
The paper contains an analytical analysis of the present situation and prospects of further development of power engineering industry inVietnamup to 2030.